REGIONAL EXPANSION IN INDONESIA: PERSPECTIVES ON DEVELOPMENT LAW THEORY - Pratama, Ganiviantara; Melati, Rima (Faculty of Law Sriwijaya University, 2023)
The research purpose is to find out the development of regional expansion in Indonesia from the point of view of development law theory. The research method used in this study indeed uses the type of juridical normative research. While the approach to be taken by the author is a statutory approach and a conceptual approach. The data analysis used by the author is descriptive qualitative data analysis. The discussion results in this study are two things: first, expansion in Indonesia is considered quite significant, primarily. This expansion is carried out in the framework of national development. But regional expansion cannot be separated from dilemmas, especially political dilemmas, administrative dilemmas, and dilemmas in terms of regional inequality. Second, regional expansion viewed from the point of view of development law theory is undoubtedly related to the role of law as a means. Law occupies a vital role in the means of regional expansion. The law plays an essential role in the legislative process of regional expansion because the autonomous regions that will secede must be based on the products of the law.